2003
DOI: 10.1002/biof.5520180213
|View full text |Cite
|
Sign up to set email alerts
|

Statins lower plasma and lymphocyte ubiquinol/ubiquinone without affecting other antioxidants and PUFA

Abstract: It has been shown that treating hypercholesterolemic patients (HPC) with statins leads to a decrease, at least in plasma, not only in cholesterol, but also in important non-sterol compounds such as ubiquinone (CoQ10), and possibly dolichols, that derive from the same biosynthetic pathway. Plasma CoQ10 decrease might result in impaired antioxidant protection, therefore leading to oxidative stress. In the present paper we investigated the levels in plasma, lymphocytes and erythrocytes, of ubiquinol and ubiquinon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
3
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 52 publications
5
23
3
1
Order By: Relevance
“…Treatment with coenzyme Q10 reverses statin-induced fatigue and neurocognitive symptoms (Langsjoen et al 2005;Passi et al 2003). Curcumin and analogues inhibit ROS-induced lipid peroxidation and protein damage in mitochondria (Wei et al 2006).…”
Section: Mitochondria As New Drug Targets In Depressionmentioning
confidence: 99%
“…Treatment with coenzyme Q10 reverses statin-induced fatigue and neurocognitive symptoms (Langsjoen et al 2005;Passi et al 2003). Curcumin and analogues inhibit ROS-induced lipid peroxidation and protein damage in mitochondria (Wei et al 2006).…”
Section: Mitochondria As New Drug Targets In Depressionmentioning
confidence: 99%
“…The widely prescribed statins block the endogenous biosynthesis both of cholesterol and of CoQ10, and the decrease in both substances is related to the does as well as the potency of these drugs (16,20). Ten mg/day of atorvastatin decreased the ubiquinol levels by 31% in plasma and by 35.2% in lymphocytes (21), and 80 mg/ day of atorvastatin decreased those in plasma by 52% (22). In the present study, the percent decrease of ubiquinol-10 level was 43.2%, and the percent decrease of total and LDL-cholesterol levels produced a proportional decrease of ubiquinol-10 and ubiquinone-10 levels.…”
Section: Reduction Of Serum Coq10 Levels By Statinmentioning
confidence: 99%
“…Littarru and Langsjoen [29] showed that simvastatin, atorvastatin, and pravastatin produced a dose-dependent plasma depletion of cholesterol and CoQ. This reduction in CoQ has also been observed in lymphocytes [30]. Mabuchi et al [28] conducted a randomized, double-blind, placebo-controlled study that examined the effects of CoQ (100 mg/d) and placebo in 49 hypercholesterolemic patients treated with 10 mg/d of atorvastatin for 16 weeks.…”
Section: In Plasma/serummentioning
confidence: 95%